Inteins—mechanism of protein splicing, emerging regulatory roles, and applications in protein engineering - Wood, David W.; Belfort, Marlene; Lennon, Christopher W. (Frontiers in Microbiology, 2023)
Protein splicing is a posttranslational process in which an intein segment excises itself from two flanking peptides, referred to as exteins. In the native context, protein splicing results in two separate protein products coupled to the activation of the intein-containing host protein. Inteins are generally described as either full-length inteins, mini-inteins or split inteins, which are differentiated by their genetic structure and features. Inteins can also be divided into three classes based on their splicing mechanisms, which differ in the location of conserved resides that mediate the splicing pathway. Although inteins were once thought to be selfish genetic elements, recent evidence suggests that inteins may confer a genetic advantage to their host cells through posttranslational regulation of their host proteins. Finally, the ability of modified inteins to splice and cleave their fused exteins has enabled many new applications in protein science and synthetic biology. In this review, we briefly cover the mechanisms of protein splicing, evidence for some inteins as environmental sensors, and intein-based applications in protein engineering.